Characterization and Optimization of Lattice-Matched InGaAs TPV Cell for Waste Heat Harvesting - Gamel M.M.A.; Ker P.J.; Lee H.J.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cells; Crystal structure; Cytology; Efficiency; Gallium alloys; III-V semiconductors; Indium alloys; Indium phosphide; Semiconducting indium; Semiconducting indium gallium arsenide; Semiconducting indium phosphide; Semiconductor alloys; Substrates; Waste heat utilization; Cell performance; Characterization; In0.53Ga0.47As; Lattice-matched; Optimisations; Performance; Radiation temperature; TPV; Waste heat harvesting; Waste heat